The Impact of Illustrations and Warnings on Solving Mathematical Word Problems Realistically - Dewolf, Tinne; Van Dooren, Wim; Ev Cimen, Emre; Verschaffel, Lieven (Journal of Experimental Education, 2014)
The present research investigated whether an illustration and/or a warning could help students to (a) build a situational model of the problem situation and (b) solve problematic word problems (P-items) that require realistic thinking more realistically. In 2 similar studies conducted in Turkey and Belgium, the authors presented 10- to 11-year-old children with several P-items. These problems were accompanied with an illustration that depicted the problem situation and/or a warning that alerted that some items may be nonstandard. Contrary to the authors' expectation, findings from both studies showed that neither the illustration nor the warning, or even the combination of both manipulations, had a positive impact on the number of realistic reactions.
Keywords: enseignement primaire; résolution de problèmes